Effects of ischemic preconditioning on sport-specific performance in highly trained taekwondo athletes - Albuquerque, M. R.; Flôr, C. A. G.; Ribeiro, A. I. S.; Mesquita, P. H. C.; Franchini, E.; Laurentino, G: C. (Sports, 2024)
Ischemic preconditioning (IPC), which involves episodes of blood flow restriction followed by reperfusion, has uncertain effects on athletes. Additionally, employing sports-specific tests that are highly familiar to athletes can enhance methodological rigor in determining IPC`s effects on taekwondo performance. This study aimed to investigate IPC`s influence on taekwondo athletes` performance through two studies. To induce occlusion in both studies, the cuff was inflated to an individualized occlusion pressure established for each athlete`s lower limb, with four cycles of occlusion lasting five minutes each, alternated with five-minute reperfusion intervals. Both traditional frequentist statistics and Bayesian analysis were employed. In the first study, eleven high-level athletes were subjected to either IPC or a placebo (SHAM) procedure on both legs, followed by performing countermovement jumps (CMJs) and a specific taekwondo endurance test. However, no significant differences were observed in taekwondo endurance performance or CMJ between the IPC and SHAM conditions. The second study involved fourteen elite athletes who underwent the same IPC or SHAM conditions, performing CMJ and three bouts of the Multiple Frequency Speed of Kick test (FSKTmult) in three blocks, each separated by approximately thirty minutes. Again, the results indicated no significant differences in FSKTmult measures or CMJ performance between the two conditions. In conclusion, IPC did not significantly affect neuromuscular (in both studies), endurance (in the first study), or anaerobic (in the second study) performance in these taekwondo athletes.